Left behind places, neoliberalism and systemic violence in the UK - Telford, Luke (Frontiers in Sociology, 2025)
Characterized by structural problems including persistent deprivation, the UK's left behind places have attracted increased scholarly, political and media attention in recent years. Throughout neoliberalism governments have implemented a range of policies to attempt to address the plight of these locales, but successful attempts at turning around their socio-economic predicaments are rather rare. One fundamental problem is that the UK has been a low investment nation across much of the neoliberal era, resulting in left behind zones not receiving the level of resourcing required to ameliorate the issues they face. This article begins by outlining how the decline of left behind places is tethered to neoliberal political economy, before discussing neoliberalism's failure to resurrect these areas. The paper then theoretically explicates left behind places in relation to systemic violence and absence. It suggests neoliberalism's inability to revive the left behind is systemically violent in its effects, resulting in a sense of political invisibility and the loss of hope. The article closes by claiming the absence of widespread political representation, engagement and a positive future among the left behind ensures the continued infliction of systemic violence.